2020
DOI: 10.1007/s10825-020-01497-3
|View full text |Cite
|
Sign up to set email alerts
|

A simulation study of the influence of a high-k insulator and source stack on the performance of a double-gate tunnel FET

Abstract: In this paper we investigate the influence of incorporating HfO2 as a dielectric at the drain side and silicon stack at the source side on the electrical performance of a double gate tunnel FET (DG-TFET). For this, we compare a conventional TFET structure with four other structures in which their gate dielectric material is either homogenous or heterogeneous while the insulator in the drain side is either SiO2 or HfO2. Moreover, a structure with silicon source stack has been proposed and the device figures of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…In this paper, prior to this work, several literatures were surveyed based on structural and material engineering [4][5][6][7][8][9][10][11][12][13][14]. The effect of homogeneous and heterogeneous material in tunneling junctions [15], effect of pocket intrinsic doping on single as well as multi gate tunneling FETs [16][17], effect of device performance based on various high-k materials [18], stress-strain effects in source-channel (n-channel) and drain-channel (pchannel) TJDs [19], usage of carbon nano-tubes (CNT) in tunneling FETs [20], nano-wire tunneling FETs [21], capacitive effects in modified TJD structures [22], various symmetric and asymmetric tunneling device structures has been studied to meet the earlier mentioned scaling issues and device performance factors.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, prior to this work, several literatures were surveyed based on structural and material engineering [4][5][6][7][8][9][10][11][12][13][14]. The effect of homogeneous and heterogeneous material in tunneling junctions [15], effect of pocket intrinsic doping on single as well as multi gate tunneling FETs [16][17], effect of device performance based on various high-k materials [18], stress-strain effects in source-channel (n-channel) and drain-channel (pchannel) TJDs [19], usage of carbon nano-tubes (CNT) in tunneling FETs [20], nano-wire tunneling FETs [21], capacitive effects in modified TJD structures [22], various symmetric and asymmetric tunneling device structures has been studied to meet the earlier mentioned scaling issues and device performance factors.…”
Section: Introductionmentioning
confidence: 99%
“…The gate dielectric plays a pivotal role in the TFET devices as it determines the extent of gate control over the channel by coupling with the gate dielectric capacitance . The studies have suggested that utilizing high-κ gate dielectrics, in contrast to silicon dioxide, can enhance the gate’s control over the channel surface and improve tunnel junction characteristics in TFETs. , Moreover, as the device dimensions decrease, reducing the thickness of the gate dielectric layer becomes imperative to effectively address the short-channel effects. However, excessively thin gate dielectric layers may induce quantum tunneling effects from the channel to the gate electrode, resulting in gate leakage current.…”
Section: Introductionmentioning
confidence: 99%
“…Source Extension-Based TFETs extend the source region beyond the gate edge to alter the electric field distribution and decrease the tunneling barrier width near the source side [11]. This boosts the pace of tunneling and promotes device function [12]. Tunnel FETs based on source extension are recognized for their straightforward fabrication and ability to enhance the ON-state current and subthreshold swing [13].…”
Section: Introductionmentioning
confidence: 99%